2004
DOI: 10.1210/jc.2003-030824
|View full text |Cite
|
Sign up to set email alerts
|

Menopause Transition: Annual Changes in Serum Hormonal Patterns over the Menstrual Cycle in Women during a Nine-Year Period Prior to Menopause

Abstract: To examine the hormonal characteristics of menstrual cycles in healthy women approaching menopause, serum hormone profiles were investigated annually in this longitudinal study of 13 healthy women between 4 and 9 yr before menopause and the year of the menopause. Serum FSH, LH, estradiol, progesterone, total inhibin, inhibins A and B, and prolactin were determined in blood samples collected annually three times weekly for 4 wk beginning with the onset of menses. Menstrual bleeding diaries covering this 4- to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 18 publications
(27 reference statements)
5
82
1
1
Order By: Relevance
“…It has been suggested that the resulting reduced negative feedback from inhibins on pituitary FSH secretion could be responsible for the observed elevated serum FSH levels in women of advanced reproductive age [76][77][78][79][80][81]. Longitudinal prospective studies have also shown age-related decline in serum inhibin B levels with advancing age during the menopausal transition [88,89].…”
Section: Menopausementioning
confidence: 99%
“…It has been suggested that the resulting reduced negative feedback from inhibins on pituitary FSH secretion could be responsible for the observed elevated serum FSH levels in women of advanced reproductive age [76][77][78][79][80][81]. Longitudinal prospective studies have also shown age-related decline in serum inhibin B levels with advancing age during the menopausal transition [88,89].…”
Section: Menopausementioning
confidence: 99%
“…Prospective studies have helped define the pattern and timing of the rise in FSH, and falls in oestradiol and the inhibins. [5][6][7] These studies have demonstrated that FSH rises and inhibin A and B fall two to three years before the menopause, while oestradiol production is maintained. The fall in inhibin A was similar to that of inhibin B but lagged it by a year.…”
Section: Need For Caution In Interpreting Hormone Resultsmentioning
confidence: 99%
“…A more detailed analysis of cycle parameters in women approaching the menopause 6 showed that ovulatory cycles occurred right up to the final menstrual period, although cycles were increasingly likely to be prolonged and anovulatory. The hormonal characteristics of the ovulatory cycles were normal, however, without elevated FSH concentrations and with normal patterns of inhibin and oestradiol production.…”
Section: Need For Caution In Interpreting Hormone Resultsmentioning
confidence: 99%
“…There is uncertainty of the menopausal status when using interview data on cessation of menses. Hormonal patterns might be more promising predictors of the menopausal status [44,45]. Biologically, cessation of menses is mainly due to the loss of ovarian follicular activity accompanied by a decrease in ovarian hormonal secretions (for review Ottolenghi et al, 2004) [46].…”
Section: Discussionmentioning
confidence: 99%